Paura e conflitto intergenerazionale durante e dopo la pandemia - Zannoni, Federico (Studi sulla Formazione/Open Journal of Education, 2021)
The event of the Covid-19 pandemic has aroused anxiety and fear on a planetary scale, generating heterogeneous reactions and behaviors, expressions primarily of the peculiar condition of individuals. The virus has affected people’s lives bringing different consequences and perspectives linked to age, employment, standard of living, people’s existential plans. The different responses to the emergency, in turn attributable to mechanisms of defense against fear, have led to the contrast between different needs and priorities and the emergence of social and cultural conflicts that were previously less obvious. Among these, it is appropriate that the pedagogical sciences pay particular attention to the divide that confronts the elderly to the younger generations, since, if not recognized with timing, it could lead to the breakdown of that intergenerational educational pact that continues to have so much value. In the pandemic crisis, the awareness of a common vulnerability could be the starting point for promoting a renewed cohesion and a dialogue between generations that can be characterized by empathy and mutual recognition.